Impact of different soil components on the infestation potential of Meloidogyne incognita in french bean (Phaseolus vulgaris) - SHARMA, G C (The Indian Journal of Agricultural Sciences, 2014)
An experiment was conducted during 1999 to study infestation potential of Meloidogyne incognita (Kofoid & White) Chitwood on french bean (Phaseolus vulgaris L.), grown in different types of soil (glasshouse conditions). Neutral soil (pH 7.09) supported the least infestation of the nematode and compared to alkaline (PH 7.97-8.69) or acidic soils (PH 6.15). Soil with highest N, P and K levels (671.1, 1 388.8 and 980 kg/ha, respectively) led the plants to minimum infestation of M incognita. Phosphorus and potassium levels in the soil individually showed their significant negative impacts on the nematode infestation. Soil with highest organic contents did support the minimum multiplication of the nematode. Coarse-textured soils were found best for the multiplication of the nematode. There was a considerable advance effect on the root nodulation (Rhizobium) due to M. incognita infestation.